2019
DOI: 10.1111/ecca.12312
|View full text |Cite
|
Sign up to set email alerts
|

Credit Constraints and the Inverted‐U Relationship Between Competition and Innovation

Abstract: Empirical studies have uncovered an inverted‐U relationship between product‐market competition and innovation. This is inconsistent with the original Schumpeterian model, where greater competition always reduces the profitability of innovation and thus the incentives to innovate. We show that the model can predict the inverted‐U if the innovators’ talent is heterogeneous and asymmetrically observable. When competition is low and profitability is high, talented innovators are credit‐constrained, since untalente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In the innovation theory of Schumpeter, there is a close relationship between market competition and corporate innovation, and innovation outcomes can be an important way for enterprises to alleviate the pressure of market share (Bonfatti and Pisano, 2020). In the product market, the degree of competition will result in the different efforts of enterprises in green innovation.…”
Section: Product Market Competition and Green Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the innovation theory of Schumpeter, there is a close relationship between market competition and corporate innovation, and innovation outcomes can be an important way for enterprises to alleviate the pressure of market share (Bonfatti and Pisano, 2020). In the product market, the degree of competition will result in the different efforts of enterprises in green innovation.…”
Section: Product Market Competition and Green Innovationmentioning
confidence: 99%
“…On the other hand, excessive competition may hinder corporate innovation, and then promote the similarity of products with reducing the profitability of enterprises. Therefore, there may be a nonlinear relationship between product market competition and green innovation (Aghion et al, 2005;Bonfatti and Pisano, 2020).…”
Section: Product Market Competition and Green Innovationmentioning
confidence: 99%
“…Finally, it will reduce the credit resources to non-urban investment enterprises. Notably, existing literature argues that a reduction in credit resources will reduce corporate R&D investment [17][18][19][20]. Specifically, in China, where the financial system is underdeveloped, bank loans are the PLOS ONE most important external financing method for corporates to obtain funds for innovative activities.…”
Section: Theoretical Hypothesismentioning
confidence: 99%
“…In this study, we explored three channels by which LGD affects corporate R&D investment. That is, (1) the LGD will consume the regional fiscal resources available to enterprises, which would reduce corporate R&D investment [11,12]; (2) the LGD will strengthen the local government collection efforts on the corporation, which would reduce corporate R&D investment [13][14][15][16]; and (3) the LGD will consume regional credit resources available to enterprises, which would reduce corporate R&D investment [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Two different research directions can be identified from these discrepancies in literature; the first is opposing views of the Arrow-Schumpeter debate and the second is the integration of both to examine the dual impacts of rivalry (Negassi et al, 2019;Bonfatti and Pisano, 2020). A strand of literature (Tang, 2006;Vives, 2008;Darai et al, 2010;Castellacci, 2011) provides empirical evidence on the relevance of the Arrow-Schumpeter debate.…”
Section: Introductionmentioning
confidence: 99%